Social perspective of apostolic exhortation Amoris laetitia - Polo Medina, Paola (2017)
This paper aims to present the Apostolic Exhortation Amoris Laetitia from two fronts under the perspective of the social dimension. First, from what today’s society brings about in the construction and transformation of the family. And, second, from the projection and presence of the family in today’s world. In this manner, focusing specially on the second chapter of Amoris Laetitia, we will consider the presence of the family in the world and the Church’s proposal and invitation to accompany families in consideration of both its faith and the human dimension